Sex and gender : a spectrum of views - Devine, Philip E.; Wolf-Devine, Celia (Wadsworth/Thomson Learning, 2003)
SEX AND GENDER: A SPECTRUM OF VIEWS provides a medium for discussion and debate about today's most provocative issues concerning human sexuality and the relationships between masculinity and femininity. Including a spectrum of views that ranges from the stridently conservative to the progressively feminist, this anthology engages students in these subjects using a wider range of standpoints than is typical of such readers.